2021
DOI: 10.29219/fnr.v65.8087
|View full text |Cite
|
Sign up to set email alerts
|

Weissella cibaria MG5285 and Lactobacillus reuteri MG5149 attenuated fat accumulation in adipose and hepatic steatosis in high-fat diet-induced C57BL/6J obese mice

Abstract: Background: Excessive consumption of dietary fat is closely related to obesity, diabetes, insulin resistance, cardiovascular disease, hypertension, and non-alcoholic fatty liver disease. Recently, probiotics have been highly proposed as biotherapeutic to treat and prevent diseases. Previously, there are studies that demonstrated the beneficial effects of probiotics against metabolic disorders, including obesity and diabetes. Objective: We investigated the anti-obesity effect and mechanism of action of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…On the other hand, according to another study, the L. reuteri MG5149 strain reduced body weight, adipose tissue weight, and adipocyte size in epididymal tissue. In addition, it inhibited the expression of lipogenic proteins such as peroxisome proliferator-activated receptor, CCAAT/enhancer-binding protein, fatty acid synthase, and adipocyte-protein 2 in some tissues and reduced fat accumulation by upregulating the phosphorylation of AMP-activated protein kinase and acetyl-CoA carboxylase [ 26 ]. Furthermore, treatment with L. reuteri JBD30l lowered the concentration of free fatty acids (FFAs) in the small intestine’s gut fluid, lowering intestinal FFA absorption while increasing fecal FFA excretion [ 27 ].…”
Section: Limosilactobacillus Reuteri and Obesity Controlmentioning
confidence: 99%
“…On the other hand, according to another study, the L. reuteri MG5149 strain reduced body weight, adipose tissue weight, and adipocyte size in epididymal tissue. In addition, it inhibited the expression of lipogenic proteins such as peroxisome proliferator-activated receptor, CCAAT/enhancer-binding protein, fatty acid synthase, and adipocyte-protein 2 in some tissues and reduced fat accumulation by upregulating the phosphorylation of AMP-activated protein kinase and acetyl-CoA carboxylase [ 26 ]. Furthermore, treatment with L. reuteri JBD30l lowered the concentration of free fatty acids (FFAs) in the small intestine’s gut fluid, lowering intestinal FFA absorption while increasing fecal FFA excretion [ 27 ].…”
Section: Limosilactobacillus Reuteri and Obesity Controlmentioning
confidence: 99%
“…Studies in mice and rats have shown, among other things, a positive effect of probiotic preparations on glucose balance [ 78 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 112 , 113 , 118 ] and reduced insulin resistance [ 78 , 87 , 89 , 90 , 91 , 92 , 94 , 113 ]. Andersson et al [ 97 ], Sakai et al [ 98 ], Park et al [ 114 ], Naito et al [ 99 ], Wang et al [ 100 , 101 ], Machado et al [ 102 ], Lee et al [ 103 ], Hsu et al [ 115 ], Kim et al [ 116 ] and Zeng et al [ 104 ] have shown that the probiotic addition of different species of the genus Lactobacillus or a combination of probiotics [ 100 , 101 , 116 ] improves glucose sensitivity (tolerance) [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 114 , 115 , 116 ] and reduces insulin resistance [ 97 , 98 , 99 , …”
Section: Effect Of Probiotics On Glucose Metabolism and Homeostasismentioning
confidence: 99%
“…The heat-inactivated probiotics containing dead cells and their metabolites can exert health-promoting biological responses, restoring the normal intestinal homeostasis, in many cases similar or even superior to that seen with live cells. , Although mechanisms underlying the beneficial effects of heat-inactivated probiotics remain inconclusive, the consistently observed benefits of inactivated probiotics may be attributed to the microbial metabolites. ,,, Here, we found that adding PKP in the culture medium successfully augmented protective effects of pasteurized L. reuteri against HFHS-induced liver injury, impaired hepatic lipid metabolism, and gut dysbacteriosis, which were superior to PKP per se and the cosupplementation of live L.…”
Section: Discussionmentioning
confidence: 73%